Fatores associados ao perfil psicossocial em gestantes de alto risco - Alcântara, Gizelda Vasconcelos Vieira de (2024)
This is an analytical cross-sectional study of high-risk pregnant women, with the aim of analysing the factors associated with the dimensions of stress, social support and self-esteem. Data was collected using the Prenatal Psychosocial Profile (PPP-VP), an instrument used internationally, translated and validated for use in Brazil, and a questionnaire designed by the researcher herself for sociodemographic and gestational data, applied in an interview format after signing the consent form. Statistical analyses were carried out, assessing absolute and relative frequency, mean and standard deviation, as well as Student's t-test, ANOVA, comparison tests, Spearman's correlation and multivariable linear regression analysis. All the pregnant women seen between May and September 2023 in a city in the interior of Goiás, totalling 123, took part in the study. The majority were aged between 18 and 29 (43.90%), most had a partner (68.30%), worked outside the home (66.70%), cohabited with their partners and/or family members (70.70%), had not planned the pregnancy (74.00%), already had up to 2 children (58.50%) and had no history of miscarriage (69.10%) or stillbirth (93.50%). The majority had no pathologies before becoming pregnant (65.00%), and for those who did, hypertension (41.90%) was the most prevalent. The average age at first pregnancy was 20.69 and the average income was 2.2 minimum wages. Most of the women received information about the risk of pregnancy (71.50%), needed to change their routine (68.30%), reported receiving help (91.90%), wanted other support (71.70%) and feared that something more serious would happen to them (74.00%). Perceived stress had a mean of 22.10±5.68, support from partners and other people 53.08±13.30 and 55.10±14.73 respectively, and self esteem 30.31±7.48, with the means of the subscales being 27.50 for stress and self esteem and 38.50 for social support from partners and other people. Predictors of stress were having a lower income, living alone or only with their children, not having received any guidance from the health team, having needed to change their routine, not having help, wanting other types of support and having needed to be hospitalised. For greater support from the partner, lower age of the pregnant woman, higher income, older age when first pregnant, no children or abortion and planned pregnancy. The greatest support from other people was having a higher income and working outside the home and self-esteem, working outside the home, not having a pathology before becoming pregnant, planned pregnancy, not having changed their life routine and not living alone or only with their children. The findings of this study show how important it is to know the psychosocial profile of a pregnant woman and the factors that can change it. High-risk prenatal care requires comprehensive care and a broad approach, taking into account all the factors that can reduce stress and improve social support and self-esteem. It is essential to think about public policies that encompass truly multidisciplinary care, which goes beyond medical follow-up, but extends to the social condition and assesses needs, based on the gestational, emotional, family, income and occupation reality.